하계 한국 남부해역 표층수의 탄산계 완충역량 - 황영빈; 이동섭; HWANG, YOUNGBEEN; LEE, TONGSUP (Pada (Hanʼguk Haeyang Hakhoe), 2022)
The buffer capacity of southern Korean waters in summer was quantified using data set of temperature, salinity, dissolved inorganic carbon, total alkalinity obtained from August 2020 cruise. The geographical distribution and variability of six buffer factors, which amended the existing Revelle factor, are discussed their relationship with the hydrological parameters of temperature and salinity. The calculated results of six buffer factors showed the spatial variations according to the distributions of various water masses. The buffer capacity was low in the East Sea Surface Mixed Water (ESMW) and South Sea Surface Mixed Water (SSMW) where upwelling occurred, and showed an intermediate value in the Yellow Sea Surface Water (YSSW). In addition, the buffer capacity increased in the order of high temperature Tsushima Warm Current (TWC) and Changjiang Diluted Water (CDW). This means that the Changjiang discharge water in summer strengthens the buffer capacity of the study area. The highest buffer capacity of CDW is due to its relatively higher temperature and biological productivity, and a summer stratification. Temperature showed a good positive correlation (R2=0.79) with buffer capacity in all water masses, whereas salinity exhibited a poor negative correlation (R2=0.30). High temperature strengthens buffer capacity through thermodynamic processes such as gas exchange and distribution of carbonate system species. In the case of salinity, the relationship with buffer capacity is reversed because salinity of the study area is not controlled by precipitation or evaporation but by a local freshwater input and mixing with upwelled water. 2020년 8월 한국 남부해역 해양 조사를 통해 수집된 수온, 염분, 용존무기탄소(DIC), 총알칼리도(TA) 자료를 사용해서 표층수의 완충역량을 정량화하였다. 기존의 Revelle 인자의 문제점을 보완한 여섯 가지 완충 인자의 지리적 분포와 변동성을 분석하고, 수문학적 요인인 수온, 염분과의 관계를 논의하였다. 모든 완충인자들은 수괴에 따른 공간적 분포를 보였다: 완충역량은 용승이 발생했던 동해표층혼합수(ESMW)와 남해표층혼합수(SSMW)에서 낮았으며, 황해표층수(YSSW)에서는 중간값을 보였다. 또한 고온인 대마난류수(TWC)와 장강희석수(CDW) 순으로 크게 나타났다. 이는 하계의 장강유출수가 연구해역의 완충역량을 강화하는 것을 의미하며, 높은 수온과 생물학적 생산력, 하계의 성층화에 의한 혼합 약화가 원인으로 판단된다. 수온-완충역량은 수괴와 상관없이 유의한 양의 상관관계(R2=0.79)를 보였으나 염분-완충역량은 약한 음의 상관관계(R2=0.30)를 보였다. 높은 수온은 열역학적 과정인 기체 교환과 탄산계 화학종 분배를 통해 완충역량을 강화한다. 염분의 경우는 연구해역의 표층 염분이 증발이나 강수가 아닌 국지적인 담수의 유입과 용승수와의 혼합에 의해 변하므로 염분과 완충역량의 관계가 역전된다.